Parietal Perfusion Alterations in Parkinson's Disease Patients Without Dementia - Pelizzari, Laura; Di Tella, Sonia; Rossetto, Federica; Laganà, Maria Marcella; Bergsland, Niels; Pirastru, Alice; Meloni, Mario; Nemni, Raffaello; Baglio, Francesca (Frontiers in Neurology, 2020)
Fronto-parietal regions are involved in cognitive processes that are commonly affected in Parkinson’s disease (PD). The aims of this study were to investigate cerebral blood flow (CBF) and gray matter (GM) volume within the regions belonging to the fronto-parietal circuit in people with PD (pwPD) without dementia, and to assess their association with cognitive performance. Twenty-seven pwPD without dementia (mean [SD] age=67.4 [8.1] years, 20 males, mean [SD] Montreal Cognitive Assessment, MoCA score=24 [2.9], median [IQR] Hoehn and Yahr scale=1.5 [1-2]) and twenty-six age- and sex-matched healthy controls (HC) were scanned with arterial spin labeling (ASL) and T1-weighted magnetic resonance imaging (MRI) sequences to investigate CBF and GM volume respectively. The cognitive performance of the enrolled pwPD was assessed with MoCA, Trail Making Test (TMT, part A, B, B-A), phonemic fluency and semantic fluency tests. The scores were adjusted for age and education. After standard preprocessing, CBF differences between pwPD and HC were tested with a voxel-wise approach. Voxel-based morphometry was used to compare pwPD and HC in terms of GM volume. Both voxel-wise comparisons between pwPD and HC were restricted to regions of the fronto-parietal circuit. The following additional voxel-wise analyses were performed within regions showing either perfusion or GM volume alterations: 1) correlation with neuropsychological test scores; 2) subgroup comparison after median split on each neuropsychological test score. Family-wise error-corrected (FWE) p-values lower than 0.05 were considered significant. Significant hypoperfusion was identified in the left inferior parietal lobule (IPL, ppeak=0.035) and in the bilateral superior parietal lobule (SPL, left hemisphere: ppeak= 0.037; right hemisphere: ppeak= 0.049) of pwPD when compared to HC. No significant GM atrophy was observed. Local hypoperfusion did not correlate with any neuropsychological test scores. However, significantly lower CBF was observed in the left SPL and IPL of the pwPD subgroup who performed poorer on TMT part A in comparison with the pwPD subgroup that performed better. Perfusion alterations may occur in parietal regions of pwPD without dementia, and may be associated with lower visuomotor skills. Parietal CBF may be considered as a suitable early biomarker for longitudinal studies investigating cognitive decline in PD.